Application of first-principles theory in ferrite phases of cemented paste backfill. (15th March 2019) - Qi, Chongchong; Fourie, Andy; Chen, Qiusong; Liu, Pengfei
Graphical abstract: Highlights: Cemented paste backfill (CPB) plays an important role in minerals engineering. Hydration in CPB relies on structural and electronic properties of cement phases. C2 F, C4 AF and C2 A were analysed and compared using first-principles calculations. Lattice parameters, bond length and angle were analysed for structural properties. PDOS, Bader charge and charge distribution were studied for electronic properties. Abstract: Cemented paste backfill (CPB) plays a vital role in mineral engineering and understanding the cement hydration is crucial for its successful application. As an important constituent in ordinary Portland cement (5–15 wt%), ferrite is heavily used in CPB without being fully demonstrated due to its composition complexity. In this paper, the structural and electronic properties of Ca2 Fe2 O5 (C2 F), Ca2 AlFeO5 (C4 AF) and Ca2 Al2 O5 (C2 A) were investigated using first-principles calculations. The results indicated that lattice parameters and bond length decreased with increasing substitution of the smaller Al 3+ for the larger Fe 3+ . The chemical reactivity of the unit cell was derived mainly from O 2 p, Fe 3 p, Fe 3 d, and Al 3 p orbitals. The O atoms were prone to electrophilic attack with cations such as H + . In contrast, the Fe/Al atoms were prone to nucleophilic attack with anions such as OH – and the Fe atoms were more reactive than the Al atoms. This study provides new insight into the structural and electronic properties of ferrite at the atomic level, which will provide a better understanding of cement hydration and promote the application of CPB.